Grandmothers' care practices in areas of high deprivation of Scotland: the potential for health promotion. (22nd July 2021) - Chambers, Stephanie A; Dobbie, Fiona; Radley, Andrew; Rowa-Dewar, Neneh
Summary: In many families grandparents play an essential role by providing secondary care for grandchildren. The family is a key setting for promoting children's health; however, studies describing health initiatives with grandparents are rare. Grandparents could play an important role in promoting health for their grandchildren within their families and communities. The aim of this study was to examine the care practices of grandparents in families living in areas of high deprivation, and to consider the extent to which grandparents could be at the centre of health-promoting initiatives for children. A family practices approach was used to examine care practices within the framework of family resource (assets/capitals) use. In-depth interviews were carried out with grandmothers ( n = 15) and mothers ( n = 15) living in areas of high deprivation in Scotland. The results are presented as three economies of family living—political, moral and emotional. Grandparent care was described as a form of social capital, central to the wellbeing of the families, and enabled parents to access education and employment. Grandparent care was supported through families' ability to access cultural amenities and green space (political). Grandparents' care practices were described as either being responsible or fun (moral). Love appeared to be at the centre of grandparents' care (emotional). The strengths and weaknesses of this framework were examined in relation to developing initiatives with grandparents. With further development work, grandparents could be the focus of health initiatives with their grandchildren with the support of appropriate policies and resources within their communities. Lay Summary: In many families, grandparents help by providing childcare. Children's health is linked to their family's overall wellbeing and there have been programmes to improve children's health within the family. These programmes do not usually include grandparents. In this study, we spoke with 15 grandmothers and 15 mothers living in Scotland about the care that grandparents provide to their grandchildren. They described the different ways in which this care was managed in relation to other aspects of family life, like work. Grandmother care was described in two main ways—as either being responsible or as fun. The main driver of grandparent care was emotional—the love grandmothers held for their grandchildren. We consider the ways in which grandparents, with appropriate support from government at different levels, might help promote health in their grandchildren.